KARAKTERISTIK ALTERASI BAWAH PERMUKAAN DI LAPANGAN PANAS BUMI “X”, KABUPATEN SUKABUMI, PROVINSI JAWA BARAT : CHARACTERISTICS ALTERATION OF SUB-SURVEY IN “X” GEOTHERMAL FIELD, SUKABUMI, WEST JAVA PROVINCE - Flaurentina Nadya; Aton Patonah; Undang Mardiana; Mochammad Nurhadi (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2022)
Indonesia is one of the countries that has the largest geothermal potential in the world. One of them is located in Sukabumi Regency, West Java. In order to optimize geothermal potential, research on geothermal characteristics is needed, one of which is the study of alteration minerals in geothermal manifestations. This research is focused on alteration studies using coring and cutting data from the drilling of Well X. The sequence of rocks in Well X from oldest to younger succession consists of lake deposits, altered tuff, altered tuff breccias, altered dacite, altered andesite, altered andesite breccias and late volcanic breccias. which is divided into two volcanic periods, namely the Pliocene period from the eruption of Mount Citorek and the Pleistocene from the eruption of Mount Halimun and Mount Tapos. Based on the assemblage of alteration minerals, the alteration zone in Well X is divided into 3 zones, namely the smectite-chlorite zone at a depth of 24 to 600 MD, illite-chlorite zone at a depth of 600 to 700 MD, and the chlorite-smectite zone at a depth of 700 to 821 MD. Based on the mineral composition and alteration zone, the type of alteration in Well X is sub-prophylitic with neutral pH and temperature 200-300°C and can act as a containment zone and judging from the appearance of manifestations controlled by the structure, the study area is in the outflow zone.